2019
DOI: 10.1249/mss.0000000000002040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Restriction on Voluntary Physical Activity Engagement in Mice

Abstract: Introduction The purpose of this study was to determine the effect of growth restriction on the biological regulation of physical activity. Methods Using a cross-fostering, protein-restricted nutritive model, mice were growth-restricted during either gestation (GUN; N = 3 litters) or postnatal life (PUN; N = 3 litters). At 21 d of age, all mice pups were weaned and fed a nonrestrictive healthy diet for the remainder of the study. At 45 d of age, mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 37 publications
6
22
1
Order By: Relevance
“…The PGR group had impairments in global cardiac function and mass (LV mass, stroke volume, cardiac output, myocardial performance index [MPI]), and diminished diastolic/systolic function (prolonged isovolumetric contraction/relaxation) in adulthood. These findings support the existing DOHaD literature, which has shown that PGR in mice impairs functional capacity of the heart, calcium flux, and exercise capacity, leading to an increased risk for CVD and mortality in adulthood [12,15,17,23,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%
“…The PGR group had impairments in global cardiac function and mass (LV mass, stroke volume, cardiac output, myocardial performance index [MPI]), and diminished diastolic/systolic function (prolonged isovolumetric contraction/relaxation) in adulthood. These findings support the existing DOHaD literature, which has shown that PGR in mice impairs functional capacity of the heart, calcium flux, and exercise capacity, leading to an increased risk for CVD and mortality in adulthood [12,15,17,23,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 90%
“…Starting at PN7, PUN pups displayed growth stunting and were 18% smaller ( P < 0.001) than the CON and GUN mice into adulthood. These observations are consistent with the literature (6,9,11,16). At completion of the investigation (PN70) female mice were smaller than male mice within each diet group (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Echocardiography and Doppler analysis are reliable tools to diagnose fibrosis (43), but future investigations should quantify cardiac tissue fibrosis via histological methods. In addition, the present investigation did not observe differences in wheel running over 3 wk between groups, but both murine (16) and human studies (44) have shown that growth restriction reduces PA in adulthood. These studies examined PA in smaller increments (i.e., 7 d) as compared with the present investigation (21 d), indicating that frequency, intensity, and type of PA should be evaluated for health benefits.…”
Section: Conclusion and Limitationscontrasting
confidence: 61%
“…16 Sections were then stained for skeletal muscle histology using previously established methods. 17 Briefly, tissue sections were permeabilized with 0.5% Triton X-100/Phosphate-buffered saline, then washed and blocked with 4% Bovine serum albumin. Sections were then probed for cell membranes with Laminin (Sigma Aldrich), BA-D5 for type I fibers (Myosin heavy chain type I, Developmental Studies Hybridoma Bank), SC-71 for type IIa cells (Myosin heavy chain type IIa, Developmental Studies Hybridoma Bank), and type IIx fibers (Unstained) overnight at 4°C.…”
Section: Vastus Lateralis Histologymentioning
confidence: 99%